Achilles Tendons Display Region-Specific Transcriptomic Signatures Associated With Distinct Mechanical Properties. Issue 14 (December 2022) - Disser, Nathaniel P.; Piacentini, Alexander N.; De Micheli, Andrea J.; Schonk, Martin M.; Yao, Vincent J.H.; Deng, Xiang-Hua; Oliver, David J.; Rodeo, Scott A.
Background: Previous studies have examined the transcriptomes and mechanical properties of whole tendons in different regions of the body. However, less is known about these characteristics within a single tendon. Purpose: To develop a regional transcriptomic atlas and evaluate the region-specific mechanical properties of Achilles tendons. Study Design: Descriptive laboratory study. Methods: Achilles tendons from 2-month-old male Sprague Dawley rats were used. Tendons were isolated and divided into proximal, middle, and distal thirds for RNA sequencing (n = 5). For mechanical testing, the Achilles muscle-tendon-calcaneus unit was mounted in a custom-designed materials testing system with the unit clamped over the musculotendinous junction (MTJ) and the calcaneus secured at 90° of dorsiflexion (n = 9). Tendons were stretched to 20 N at a constant speed of 0.0167 mm/s. Cross-sectional area, strain, stress, and Young modulus were determined in each tendon region. Results: An open-access, interactive transcriptional atlas was generated that revealed distinct gene expression signatures in each tendon region. The proximal and distal regions had the largest differences in gene expression, with 2596 genes significantly differentially regulated at least 1.5-fold ( q < .01). The proximal tendon displayed increased expression of genes resembling a tendon phenotype and increased expression of nerve cell markers. The distal region displayed increases in genes involved in extracellular matrix synthesis and remodeling, immune cell regulation, and a phenotype similar to cartilage and bone. There was a 3.72-fold increase in Young modulus from the proximal to middle region ( P < .01) and an additional 1.34-fold increase from the middle to distal region ( P = .027). Conclusion: Within a single tendon, there are region-specific transcriptomic signatures and mechanical properties, and there is likely a gradient in the biological and functional phenotype from the proximal origin at the MTJ to the distal insertion at the enthesis. Clinical Relevance: These findings improve our understanding of the underlying biological heterogeneity of tendon tissue and will help inform the future targeted use of regenerative medicine and tissue engineering strategies for patients with tendon disorders.